(untitled) (Książnica Śląska, 2025)
The author, basing herself mainly on documents from the Archive of the Silesian Library, described the participation of the Silesian Public Library during the securing libraries and library collections in the Silesian Voivodeship in the years 1945–1947. She presented the legal and organizational basis and participants of the action, as well as its course and financing. The author described the effects of almost two years of activity in the field of searching, recovering, saving from destruction and dispersion valuable book collections that had been moved, leaved or abandoned in the Recovered Territories.